2019
DOI: 10.3892/etm.2019.8083
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanol alleviates myocardial injury in diabetic db/db mice by regulating the SIRT1/HMGB1/NF‑κB signaling pathway

Abstract: Myocardial injury induced by diabetes has become an increasing health problem. Chrysophanol (CHR) has been widely studied as a potential treatment for many diseases due to its anti-inflammatory effects, but has not been investigated in regard to diabetes-induced myocardial injury. The present study evaluated the myocardial protective effects of CHR in C57BL/KsJ-db/db diabetic mice. C57BL/KsJ-db/db and C57BLKS/J mice were treated with vehicle, metformin (100 mg/kg/day) or CHR (50 or 100 mg/kg/day) for 28 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Meanwhile, CHR could protect diabetic mice from myocardial injury via mediation of SIRT1/HMGB1/ NF-κB signaling pathway. 16 However, our current study found CHR could mediate TGF-β signaling in DN. The difference may due to different types of diabetes complications.…”
Section: Discussioncontrasting
confidence: 67%
“…Meanwhile, CHR could protect diabetic mice from myocardial injury via mediation of SIRT1/HMGB1/ NF-κB signaling pathway. 16 However, our current study found CHR could mediate TGF-β signaling in DN. The difference may due to different types of diabetes complications.…”
Section: Discussioncontrasting
confidence: 67%
“…Oxidative stress stimulates NF-jB and causes translocation of NF-jB to the nucleus [37]. In addition, there are studies shown that SIRT1 affects NF-jB signalling pathway [38][39]. So we next detect whether miR-217 affects NF-jB signalling pathway through regulating SIRT1 and then plays important roles in H 2 O 2 -treated melanocytes.…”
Section: Down-regulation Of Mir-217 Inhibited Nf-jb Activation In H 2mentioning
confidence: 97%
“…Systemic inflammation is often associated with obesity/insulin resistance, T1DM, and T2DM [51][52][53]. DM animal models such as STZinduced and db/db mice presented with upregulated proinflammatory cytokines such as TNF-α, IL-6, and IL-1β compared to normal mice [36,54]. Diabetes-induced myocardial injury was highly correlated with serum and myocardial proinflammatory cytokines [54].…”
Section: Plos Onementioning
confidence: 99%